Soil erosion dynamic monitoring in the Northeast Inner Mongolia of China from 1978 to 2018. Issue 1 (1st March 2022) - Jiang, Wei; Pang, Zhiguo; Qin, Xiangdong; Ju, Hongrun; Xiaohui, Ding; Li, Lin; Fu, June; Li, Hao; Lu, Jingxuan; Feng, Tianshi
Abstract: The black soil area in Northeast Inner Mongolia is an important ecological barrier and food production base in China and the soil erosion is a key risk factor in regional ecological security and sustainable development. Multi-source satellite remote sensing and auxiliary data, including meteorology, land use, vegetation coverage and digital elevation were collected to establish a distributed model of soil erosion. Then, the quantitative analysis of soil erosion in the Northeast Inner Mongolia from 1978 to 2018 was carried out. The results show the following: (1) the areas of soil erosion in 1978 and 2018 were 203, 538 km 2 and 102, 886 km 2 respectively, and the area of soil erosion was decreased by 100, 653 km 2 . The decreased of soil erosion was mainly located in the Songliao Plain Sand Prevention Farmland Protection Zone; (2) wind erosion is the main erosion type in the Northeast Inner Mongolia. Wind erosion area decreased from 188, 982 km 2 in 1978 to 88, 466 km 2 in 2018, and water erosion area decreased from 14, 556 km 2 in 1978 to 14, 420 km 2 in 2018.(3) the intensity of soil erosion is mainly mild. The area change rates of mild, moderate, strong, intensive and severe soil erosion intensity are -48.91%, -41.41%, 32.63%, -91.15% and -91.14% respectively. This study demonstrated how to use multi-source remote sensing technology to explore the long term series soil erosion dynamic monitoring and provided support for decision-making and management of soil erosion in Northeast Inner Mongolia under the background of sustainable development.